PERAN PEMUDA DALAM KEGIATAN BUDIDAYA HIU ZEBRA (Stegostoma fasciatum) BERBASIS MINAWISATA DI DESA TAWIRI KOTA AMBON - Grace Tuhumury; Jacob W Mosse; Renoldy L Papilaya (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2020)
Minawisata is the integration of the potential of capture fisheries, aquaculture and marine tourism in an integrated management model based on conservation. With this concept of minawisata bridge the interests of various parties based on community welfare and the sustainability of natural resources. This study aims to identify and analyze the role of youth in cultivation activities. The zebra shark (S. fasciatum) is based on minawisata (fish feeding). The research method used qualitative methods and quantitative methods using primary data sources that were obtained directly in the field (interviewing 50 respondents) and secondary data sources obtained from libraries. Data analysis was using Microsoft Excel to analyze water quality data and using Path analysis to analyze the role youth in Bebabasis Minawisata cultivation. The results showed, the role of youth in cultivation activities of Zebra Sharks (S. fasciatum), namely youth participation of 8.74% and youth perceptions of 3.4% while the role of youth in fish feeding minawisata is 76.3% youth participation, youth perception 5, 3% and cultivation of 3.5%.